Microsoft 365 Endpoint Administrator Associate (MD-102) Cert Prep: 3 Manage, Maintain, and Protect Devices. - Warren, Andrew; Press, Microsoft (linkedin.com, 2023)
Prepare for the MD-102 Endpoint Administrator exam and manage devices and client applications more effectively, with a focus on managing, maintaining, and protecting devices.